Assessing regional integration: The progress of ASEAN regional grouping - Ibrahim, Fatimah Wati (2007)
The Association of Southeast Asian Nations (ASEAN) is now entering a new phase in its integration process. Beyond AFTA, it is now preparing a roadmap towards deeper economic integration, namely the creation of an ASEAN Economic Community by 2015. Economic integration is to be encouraged if it can contribute positively towards the achievement of this goal and the overall developmental goals of the ASEAN countries. In view of the importance of enhancing economic integration in the era of globalisation, this paper evaluates the progress of ASEAN regional integration for the past decade to see to what extent ASEAN economic integration efforts have been successful. In this paper, the progress and developments of ASEAN countries are evaluated using performance indicators of regional integration based on ASEAN economic integration index. The scope of analysis of economic integration focuses on the three most important sectors of the thrusts of ASEAN economic cooperation, that is, trade; Investment; and human resources and labour mobility.